Integrating 'Approval to Post' into HCM Systems : Enhancing Efficiency and Transparency through Workday Solutions - Shweta Pandey; Sumit Pandey (North American Journal of Engineering Research, 2021)
In today’s corporate world, effective cost management is crucial across industries. Employees are both valuable assets and significant expenses, particularly highlighted post-Covid-19. Companies now carefully approve new hires or replacements, yet the process often occurs outside Human Capital Management (HCM) platforms, causing reporting gaps and inefficiencies. This article explores using questionnaires, approval frameworks, and business process workflows to track and manage "Approval to Post" within HCM systems, with a focus on Workday’s tools and solutions to optimize these processes.